Physical oceanography during GOAL cruise PATEX (2004, 2006, 2007, 2008 and 2009) - Carlos Alberto Eiras Garcia; Virginia Maria Tavano; Mauricio M Mata (PANGAEA, 2025)
This dataset contains temperature, salinity, fluorescence, and dissolved oxygen measurements collected from 2004 to 2009 in the Patagonian shelf, between 35 and 55 degrees of south latitude. During this period, a total of 7 cruises were carried out in the area by the High Latitude Oceanography Group (GOAL-FURG). The Patagonian Experiment (PATEX) aims to collect biogeochemical and bio-optic data in the Patagonian shelf that will allow for a detailed study of microalgae blooms and quantitatively infer the importance of marine microalgae in the regional carbon cycle and exchanges of gases relevant to the greenhouse effect. Salinity and temperature were measured using CTD (conductivity, temperature, and depth), and fluorescence and dissolved oxygen were obtained using auxiliary sensors installed in the CTD.